A Novel Human Cytomegalovirus Glycoprotein, gpUS9, Which Promotes Cell-to-Cell Spread in Polarized Epithelial Cells, Colocalizes with the Cytoskeletal Proteins E-Cadherin and F-Actin - Maidji, Ekaterina (American Society for Microbiology, 1998)
Processes by which human herpesviruses penetrate and are released from polarized epithelial cells, which have distinct apical and basolateral membrane domains differing in protein and lipid content, are poorly understood. We recently reported that human cytomegalovirus (CMV) mutants with deletions of the gene US9 formed wild-type plaques in cultures of human fibroblasts but were impaired in the capacity for cell-to-cell spread in polarized human retinal pigment epithelial cells. Unlike the glycoproteins that are required for infection, the protein encoded by CMV US9 plays an accessory role by promoting dissemination of virus across cell-cell junctions of polarized epithelial cells. To identify the product and investigate its specialized functions, we selected Madine-Darby canine kidney II (MDCK) epithelial cells that constitutively express CMV US9 or, as a control, US8. The gene products, designated gpUS9 and gpUS8, were glycosylated proteins of comparable molecular masses but differed considerably in intracellular distribution and solubility. Immunofluorescence laser scanning confocal microscopy indicated that, like gpUS8, gpUS9 was present in the endoplasmic reticulum and Golgi compartments of nonpolarized cells. In polarized epithelial cells, gpUS9 also accumulated along lateral membranes, colocalizing with cadherin and actin, and was insoluble in Triton X-100, a property shared with proteins that associate with the cytoskeleton. We hypothesize that gpUS9 may enhance the dissemination of CMV in infected epithelial tissues by associating with the cytoskeletal matrix.